Problem Teoretis Dualisme Penguasaan dan Kepemilikan dalam Jaminan Fidusia: Kritik terhadap Konstruksi Transfer of Ownership Secara Fidusia - Syafira Putri Ayu Dewantari; Siti Malikhatun Badriyah (Jurnal Ragam Pengabdian, 2026)
This article examines the theoretical inconsistency embedded in the construction of fiduciary security under Indonesian law, particularly the tension between juridical ownership and factual possession arising from the doctrine of transfer of ownership by way of fiduciary. The study addresses the question of whether fiduciary transfer genuinely creates proprietary rights or merely functions as a legal fiction to secure debt performance. The research is doctrinal and non-empirical, relying on statutory analysis of the Fiduciary Security Law, related bankruptcy regulations, and constitutional jurisprudence, supported by doctrinal literature and comparative insights from modern secured transactions regimes. Legal materials were collected through document-based research and analyzed using systematic, teleological, and conceptual interpretation combined with coherence-based normative evaluation. The findings demonstrate that fiduciary ownership in Indonesian law does not operate as absolute proprietary control, since risk allocation, execution constraints, third-party protection, and constitutional limitations all indicate that the debtor retains substantive economic ownership. This structural dualism reveals that fiduciary transfer of ownership functions primarily as an instrumental legal device rather than a true conveyance of title. The study concludes that fiduciary security should be reconceptualized as a sui generis security right grounded in priority and value protection rather than formal ownership transfer. Such a reconstruction would enhance doctrinal coherence, improve legal certainty, and align Indonesian security law with contemporary global secured transactions principles.